Tecnologia e trabalho: panorama atual da institucionalização do teletrabalho na justiça do trabalho brasileira - Amorim, Ana Karine Uchôa Leite Brito (2020)
The following research deals with a study on the current institutionalization of teleworking’s outlook in the Brazilian Labor Court and it’s general objective is to analyze how the Superior Labor Court and the Regional Labor Courts of the 2nd Region – São Paulo, of the 9th Region – Paraná, of 11th Region – Amazonas and Roraima, from the 18th Region - Goiás and the 22nd Region – Piauí ideal with teleworking regime in their internal regulations regarding the variables telework management, Technologies and teleworker civil servants of the Labor Court. These Courts were chosen based on evaluation criteria so that the five Brazilian regions could have representation in the current scenario of institutionalizing telework in the Labor Court. The definition contained in Resolution CSJT Nº 151/2015 was adopted as a concept for telework, which is namely: “telework: modality of work carried outside the premises of the first and second degree Labor Courts, with the use of technological resources”. This research was developed through bibliographic review and document analyses. Among the authors who contributed to the literature review, the following stand out: De Masi (2000, 2001, 2018); Goulart (2009); Mello (1999); Nilles (1997); Nunes (2018) and Trope (1999). Afterwards, the documents to be analyzed analyzed were mapped, namely: Administrative Resolution TST Nº 1.970, of March 20, 2018 and the regulations of the Regional Labor Courts of the 2nd Region (Act GP Nº 56/2018), 9th Region (Act Nº 199/2018), 11th Region (Administrative Resolution Nº 160/2016) and 22nd Region (Administrative Resolution Nº 22/2018). The result of this research points to the current overview of the institutionalization of teleworking in the Brazilian Labor Court, evidencing the viability and acceptance of the teleworking regime by the Labor Justice server, since all the bodies of this specialized justice system have teleworkers. The analysis of the regulations showed that, to a large majority, the contents of the regulations are aligned with the guidelines found in the bibliographic reference, at the same time that they revealed that they are challenges and opportunities for improvements in the teleworking regime instituted in the Labor Justice Bodies. It can also be understood that the researched bodies describe, in their regulations, the operationalization of teleworking in a very similar way, with a few particularities in different government bodies.